Diseases caused by defects of energy level and loss of coherence in living cells. (June 2015) - Jandová, Anna; Pokorný, Jan; Pokorný, Jiří; Kobilková, Jitka; Nedbalová, Martina; Čoček, Aleš; Jelínek, František; Vrba, Jan; Vrba, Jan; Dohnalová, Alena; Kytnarová, Jitka; Tuszyński, Jack A.; et al.
Abstract Human and animal diseases are brought about by pathological alterations of production, composition, and conformation of macromolecules and structures in cells. Additional contributing factors include changes in physiological states caused by disturbances of energy supply, energy transduction, energy dissipation in moving or oscillating parts, and parasitic energy consumption. Disturbances of energy states may endanger existence of the system. The cell-mediated immunity (CMI) response of T lymphocytes correlating with their adherence properties was examined using antigen prepared from the serum of inbred laboratory mice strain C3H H2k infected with lactate dehydrogenase elevating (LDH) virus. LDH virus is a parasite on the cellular energy system. Significant CMI response was elicited in T lymphocytes prepared from the blood of patients with cancer of different phenotypes, acute myocardial infarctions, schizophrenia, and recurrent spontaneous abortions in early pregnancy from unknown reasons. The CMI response is assumed to monitor transferred information about decreased levels of energy states and decoherence in the cells caused by mitochondrial malfunction, parasitic consumption, production of lactate, and possibly other disturbances. The LDH virus infection or similar pathological processes caused by different agents might be connected with the diseases and monitored by the examined CMI response. A large amount of mitoses with chromosome defects in aborted fetuses suggest increased mutability of genomes caused by defective energy states.